Effect of hybrid drying technique on non-traditional Chicory (Cichorium intybus L.) herb: Phytochemical, antioxidant characteristics, and optimization of process conditions - Zahoor, Insha; Anjum, Nadira; Ganaie, Tariq Ahmad; Allai, Farhana Mehraj; Al-Ghamdi, Abdullah Ahmed; Abbasi, Arshad Mehmood; Wani, Sajad Ahmad (Frontiers in Sustainable Food Systems, 2022)
This research investigated the influence of microwave-assisted fluidized bed drying (MAFBD) on the antioxidant and phytochemical characteristics of Chicory. Microwave power, temperature, and air velocity were used as process variables varied between 180–540 W, 50–70 °C, and 15–20 m/s, respectively. The responses determined for deciding the optimal criteria were total phenolics content, ascorbic acid, DPPH radical scavenging activity, total chlorophyll, carotene content, total flavonoid content, tannin content, and saponin content of the dried chicory. Statistical analyses were done by using the response surface methodology, which showed that independent variables affected the responses to a varied extent. The design expert predicted 462.30 W microwave power, 70°C temperature, and 15 m/s air velocity as optimum conditions to obtain highest desirability for the dried chicory. Separate validation experiments were conducted, under optimum conditions, to verify the predictions and adequacy of the second-order polynomial models. Under these optimal conditions, the predicted amount of ascorbic acid content was 38.32 mg/100g DW, total phenolic content 216.42 mg/100g DW, total flavonoid content mg/100g DW, DPPH scavenging activity 36.10 μg/ml, total chlorophyll content 311.79 mg/100g, carotene content 7.30 mg/100g, tannin content 2.72 mg/100g, and saponin content 0.46 mg/100g. The investigated parameters had a significant effect on the quality of the dried chicory. Taking the aforesaid results into consideration, our study recommended MAFBD as a promising technique with minimum changes in antioxidant and phytochemical content of chicory.